2000
DOI: 10.1210/jcem.85.8.6738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Treatment with Metformin Added to Hypocaloric Diet on Body Composition, Fat Distribution, and Androgen and Insulin Levels in Abdominally Obese Women with and without the Polycystic Ovary Syndrome

Abstract: Abdominal obesity and hyperinsulinemia play a key role in the development of the polycystic ovary syndrome (PCOS). Dietary-induced weight loss and the administration of insulin-lowering drugs, such as metformin, are usually followed by improved hyperandrogenism and related clinical abnormalities. This study was carried out to evaluate the effects of combined hypocaloric diet and metformin on body weight, fat distribution, the glucose-insulin system, and hormones in a group of 20 obese PCOS women [body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
231
3
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(268 citation statements)
references
References 25 publications
19
231
3
6
Order By: Relevance
“…Unfortunately, only one study of LCD and one of LCD þ sibutramine provide data at 4 weeks for comparison. 16,59 These studies show only mild %dV/%dS (1.28 and 1.39) at this time point, suggesting that early elevated %dV/%dS is associated with VLCDs. Interestingly, among studies in which subjects were followed up after 12-14 weeks, VLCDs had caused greater weight loss and lower %dV/%dS than other studies at this time point (Figure 3).…”
Section: Discussionmentioning
confidence: 70%
“…Unfortunately, only one study of LCD and one of LCD þ sibutramine provide data at 4 weeks for comparison. 16,59 These studies show only mild %dV/%dS (1.28 and 1.39) at this time point, suggesting that early elevated %dV/%dS is associated with VLCDs. Interestingly, among studies in which subjects were followed up after 12-14 weeks, VLCDs had caused greater weight loss and lower %dV/%dS than other studies at this time point (Figure 3).…”
Section: Discussionmentioning
confidence: 70%
“…80 Weight, waist and BMI were reduced in all groups (Po0.0001). Small 7-month studies in nondiabetic overweight (BMI 428 kg/m 2 ) 81 or morbidly obese subjects (mean BMI 43 kg/m 2 ) 82 demonstrated decreases in body weight with metformin, although only the latter study demonstrated a reduction in waist circumference. Two of the studies summarized in Table 3 suggest a greater weight reduction with metformin relative to placebo, but these differences did not achieve statistical significance.…”
Section: Effects Of Metformin On Body Weight In Nondiabetic Patientsmentioning
confidence: 96%
“…[79][80][81][82] The first Biguanides and Prevention of the Risks in Obesity study 1 enrolled 324 patients with abdominal obesity (waist-hip ratio X0.95 in men and X0.80 in women) in order to recruit a trial population containing a high prevalence of insulin resistance. 79 Subjects were also free of cardiovascular disease and diabetes at baseline.…”
Section: Effects Of Metformin On Body Weight In Nondiabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS is a heterogeneous disorder, characterised by hyperandrogenism, chronic anovulation and infertility [2][3][4][5]. A significant proportion of PCOS women suffer from insulin resistance, which appears to play a role in the aetiology of PCOS, since amelioration of insulin resistance by lifestyle or pharmacological intervention has been shown to improve hyperandrogenism and fertility [6][7][8][9]. Furthermore, insulin resistance is proposed to be a major risk factor for the development of type 2 diabetes mellitus and subsequent cardiovascular disease [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%